Experimental Investigation on Jacked Pile-Sinking and Capacity-Induced Pore Pressure and Effective Radial Stress at the Pile-Clayey Soil Interface - Wang Lifeng; Wang Xin; Li Shiqiang; Wang Jun; Niu Xunlong; Wang Donglei; Yonghong Wang (Advances in Civil Engineering)
Based on research into how static pressure piles sink in saturated cohesive soil, alterations caused by a rise in pore stress during the load process between the pile and the earth as well as the effects of a variation in valid radial thrust on the project are thoroughly studied. These changes are of great importance for the application and practice of practical projects. Microtest components are embedded on the surfaces of open and closed piles, and test research is conducted using a large-scale system and double-deck open and closed pipe piles. Finally, complete consideration is given to how variations in effective radial stress. Through this test, it was determined that as the pile’s buried depth gradually grows, so do the valid radial thrust and excess pore pressure. However, the quantity of the superfluous pore water stress for a closed pile is higher than for an open pile. And the higher half has substantially lower effective radial thrust and overall surplus pore stress than the lower part does. The pile penetration depth is constant, and the value of h/L of the pile shaft is also rising, the occurrence of “lateral pressure degradation” of earth load between pile and earth is becoming increasingly prominent. The maximum ratio of the excess pore stress to the valid soil pressure between the pile and earth contact is 62.1% for an exposed pile and 52.1% for a sealed pile. At the interface, the effective radial stress is about 3.76∼5.46 times that of the remaining pore water stress. Therefore, under changing pile penetration depths, the value of h/L will have an impact on the pile’s and the soil’s additional pore water pressure or excellent soil pressure. The test results have a significant impact on how static pressure piles are built and how bearing capacity is designed in real-world applications.